"153Sm-EDTMР, solution for therapy" was tested on rats in the experimental study in radioactivity equivalent to human. (Experimental biology, 2016)
The article presents the results of tests on rats new domestic osteotropic drug "153Sm-EDTMP, solution for therapy", produced by the Institute of nuclear physics, intended for radionuclide therapy of metastases of malignant tumors and inflammation in the bones. Studied the picture of peripheral blood and bone marrow in 7 subjects who entered the dose of radioactivity "153Sm-EDTMP, solution for therapy", is equivalent to man and 5 intact control rats. Indicators median hemoglobin, a color indicator, segmented neutrophils and leukocytes were higher and platelets, monocytes, and lymphocytes from subjects less rats than in the controls. Marked thrombocytopenia, as one of the signs of the damaging effect of radiation on the organism, in rats that received radioactive. In the red bone marrow of the subjects of the rats revealed an increase in cellularity, changes in the ratios of the germs of hematopoiesis, the extension of the red Rostock dyserythropoiesis, increased number of megakaryocytes. Platelets were ethnoregionalist in sufficient quantity and type of hematopoiesis normoblasticheskuyu as in the control rats.
Keywords: radionuclide therapy; bone metastases; experimental study; equivalent radioactivity; periferal blood; bone marrow.